Apomorphine in the treatment of Parkinson's disease: a review - Renata Ramina Pessoa; Adriana Moro; Renato Puppi Munhoz; Hélio A.G. Teive; Andrew J. Lees (Arquivos de Neuro-Psiquiatria)
ABSTRACT Optimizing idiopathic Parkinson's disease treatment is a challenging, multifaceted and continuous process with direct impact on patients’ quality of life. The basic tenet of this task entails tailored therapy, allowing for optimal motor function with the fewest adverse effects. Apomorphine, a dopamine agonist used as rescue therapy for patients with motor fluctuations, with potential positive effects on nonmotor symptoms, is the only antiparkinsonian agent whose capacity to control motor symptoms is comparable to that of levodopa. Subcutaneous administration, either as an intermittent injection or as continuous infusion, appears to be the most effective and tolerable route. This review summarizes the historical background, structure, mechanism of action, indications, contraindications and side effects, compares apomorphine infusion therapy with other treatments, such as oral therapy, deep brain stimulation and continuous enteral infusion of levodopa/carbidopa gel, and gives practical instructions on how to initiate treatment.